Bioethanol Dehydration Process using NaOH-Activated Zeolite at Various Concentration and Zeolite Weight - Saidi, David; Jannah, Akyunul; Maunatin, Anik (ALCHEMY, 2015)
Utilization of molasses as basic material for producing bioethanol becomes one of the promising efforts to fulfill the demand of fuel and diminish the dependence upon fossil fuel that its availability is increasingly rare. However, ethanol produced from fermentation of molasses has low purity. The purity could be increased by using dehydration method and zeolite activated by NaOH and alum as alumina source. The research is aimed to know the dehydration process of bioethanol use NaOH-activated zeolite at various concentration and zeolite weight on the purification of bioethanol. In this research, the experiments could be categorized into 4 groups, they are activation of zeolite, fermentation, distillation, and dehydration process. Activation of natural zeolite performed by entering of sized 120-150 mesh zeolite powder was added to glass beaker that containsÂ  NaOH aqueous solution and followed by adding alum which took place at 80 ËšC for 8 hours and the final product calcinated at 600 Ëš C for 2 hour. Fermentation process was managed for 6 days and pH 5. Furthermore, bioethanol was separated by distillation method at 78,5 - 85 ËšC and followed by molecular sieve dehydration using zeolite activated by NaOH solution in variation of zeolite weight (30, 40 and 50 %) and NaOH concentration (1, 2, 3 dan 4 M). The amount of bioethanol was measured by gas chromatography method. Bioethanol concentration as fermentation product is 29,8 %. The result revealed that dehydration with 30% w.t zeolite activated by 2 M NaOH solution had the best activity in bioethanol purification with amount of bioethanol is 53,76 %, Increased Levels of Bioethanol (ILB) value is 80,39 % and Adsorption Capacity of Zeolite (ACZ) is 399,31 %.Keywords: bioethanol, concentration of NaOH, dehydration, molasses, molecular sieve, weight of zeolite